The Effect Of Gargling Green Tea On Salivary Flow Rate On Female With Xerostomia At Puskesmas Darussalam Medan - Lubis, Wilda Hafny; Tampubolon, Kiky Erika; Saragih, Awaluddin (IIUM Medical Journal Malaysia, 2017)
Introduction: Saliva is important in maintaining the health of the oral environment. A reduction of the saliva flow by 40% to 50% will cause xerostomia. Xerostomia as the main complaint, experience by about 14%-46% of patients. The objective of this research is to find out the influence of green tea gargle to saliva flow rate in xerostomia patient. Materials and Methods: Green tea with the Latin name Camellia sinensis (L). Polyphenol compounds, catechins in this tea cause a bitter taste that can stimulate the central nervous system resulting in increased salivary secretion. Green tea weighing 3 grams, brewed with 20 ml of hot water an let to stand for 5 minutes then strained and used it for gargeling. The subjects of the study were female of Puskesmas Darussalam visitors. The sample was selected using purposive sampling method and they consisted of 20 people for gargling group of green tea and 20 for gargeling aquades. Saliva was obtained by spitting method. Results: The mean difference in salivary flow rate gargling the aquades was about 0.033350 ml / min, while the mean difference of salivary flow rate gargling the green tea was about 0.281750 ml/min. The statistical T test was unpaired, p = 0,000 difference in mean difference of salivary flow rate was significant, between treatment group and control group. Conclusion(s): The group with green tea gargeling was better in stimulating salivary flow rate.